ETWatch cloud: APIs for regional actual evapotranspiration data generation. (November 2021) - Wu, Fangming; Wu, Bingfang; Zhu, Weiwei; Yan, Nana; Ma, Zonghan; Wang, Linjiang; Lu, Yuming; Xu, Jiaming
Abstract: Increased model complexity and data quantities have raised the computing power requirement for efficient evapotranspiration (ET) estimation. A cloud-based service is presented to encapsulate and publish the ETWatch modeling algorithms as web application programming interfaces (APIs) in a consistent style to provide extensible model calculation service and data storage service in a cloud platform for water managers and stakeholders. The prototype system, named ETWatch Cloud allows users to rapidly and easily set up an ET generation project for any region of interest by invoking APIs directly to produce ET data using a web browser or local integrated development environment. The case study demonstrates that ETWatch Cloud can provide a highly scalable and interoperable ET generation tool for stakeholders from ET community, helping to facilitate the application of remote sensing-based ET algorithms for water management in hydrology sector. Highlights: A new high scalability, easy interoperability, cloud-based for ET generation at reginal scale. Encapsule and publish ETWatch modeling algorithm to web API in a consistent style. A general solution for the publishing, running and management of modules in the cloud. Provides stakeholders in the ET community and hydrology sector with an innovative tool. Generate ET data without additional computing, storage, or algorithm development.